2013
DOI: 10.1177/1359105313475902
|View full text |Cite
|
Sign up to set email alerts
|

A problem-solving education intervention in caregivers and patients during allogeneic hematopoietic stem cell transplantation

Abstract: The aim of this study was to determine the effect of problem-solving education on self-efficacy and distress in informal caregivers of allogeneic hematopoietic stem cell transplantation patients. Patient/caregiver teams attended three 1-hour problem-solving education sessions to help cope with problems during hematopoietic stem cell transplantation. Primary measures included the Cancer Self-Efficacy Scale–transplant and Brief Symptom Inventory–18. Active caregivers reported improvements in self-efficacy (p < 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 48 publications
3
57
0
5
Order By: Relevance
“…A "dose-response" of behavior changes according to the number of educational modules received has been reported in other behavior interventions similar to the MPP. [43][44][45] The MPP effectiveness in reducing HF outcomes is also consistent with other educational intervention studies in which intervention "compliance" has an important role in determining efficacy.…”
Section: %supporting
confidence: 79%
See 1 more Smart Citation
“…A "dose-response" of behavior changes according to the number of educational modules received has been reported in other behavior interventions similar to the MPP. [43][44][45] The MPP effectiveness in reducing HF outcomes is also consistent with other educational intervention studies in which intervention "compliance" has an important role in determining efficacy.…”
Section: %supporting
confidence: 79%
“…Many studies have found a "dose effect" with educational interventions for disease management in which the number of lessons received or attended was associated with better clinical outcomes. [43][44][45] This is especially important for severe and complicated medical conditions, such as HF, in which it is important that patients learn about and manage all aspects related to their medical condition (e.g., complex medication regime, drastic sodium reduction in diet, and reducing edema). A "dose-response" of behavior changes according to the number of educational modules received has been reported in other behavior interventions similar to the MPP.…”
Section: %mentioning
confidence: 99%
“…Limited interventions such as education, psychosocial support, and self-care for the family caregivers of HSCT recipients have been reported (Gemmill et al, 2011). Recently, it has been showed that caregivers participating in a problem-solving form of education during HSCT period increased their self-efficacy and they had reduced symptoms distress (Bevans et al, 2014). Because the family member has the highest distress in pre-transplant period (Beattie and Lebel, 2011) we suggest that they would benefit from more targeted support during this phase, to boost them to prevent and handle the uncertainty during the HSCT.…”
Section: Discussionmentioning
confidence: 84%
“…With these points in mind, comprehensive long-term follow-up units aimed specifically at alloHCT survivors have shown evidence of efficacy [119•]. Interventions for caregivers may similarly ease the burdens of alloHCT survivorship [127,128].…”
Section: Othermentioning
confidence: 99%